STUDI KOROSIVITAS DAN MORFOLOGI PERMUKAAN BAJA KARBON API 5L GR-B YANG DILAPISI POLIMER HIBRID PADA LINGKUNGAN AIR LAUT DAN GAS H2S PADA KONDISI JENUH CO2 - Setiawidiani, Dinar; Susilawati, Tuti; Suryaningsih, Sri; Harjo, Hardoyo (BERKALA FISIKA, 2014)
It has been tested with the corrosion protection of carbon steel using hybrid inorganic - organic polymer. Hybrid polymer precursor materials is synthesized from monomers poly (TMSPMA) using sol- gel technique. The hybrid polymer precursors coated on the surface of carbon steel API 5L GR - B, and then thermally polymerized. Corrosion test conducted in a seawater environment, H2S, CO2 saturation using potentiodynamic polarization method and morphological examination using a Scanning Electron Microscope. The obtained results shows the corrosion rate of carbon steel without coating in critical condition was 1.643 mm/year. Once the hybrid polymer coated carbon steel with a corrosion rate becomes 0.903 mm/year. The corrosion rate was reduced to 0.74 mm/year. Corrosion rate is related to the protection efficiency of 45.05%. These results are supported by data that shows the surface morphology uneven corrosion on carbon steel surface after coated with polymer hybrid. Keywords : corrosion , carbon steel , polymer hybrid , potentiodynamic polarization